2020
DOI: 10.2991/efood.k.200909.001
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Methods to Evaluate Anthocyanins

Abstract: Anthocyanins are one of the most important water-soluble pigments in the nature. Interests in the research of anthocyanins are increasing due to its nutritional value and biological activity. Extraction, separation and qualitative and quantitative analysis of anthocyanins are indispensable and important results in the study of anthocyanins. This article briefly outlines the main extraction processes of anthocyanins, focusing on describing the qualitative and quantitative analysis methods of anthocyanins in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 27 publications
1
20
0
2
Order By: Relevance
“…But there were no other ion fragments appeared, which showed that the mother nuclear stability of C3G was strong. Besides, the acylation occurred on glucoside, which was consistent with previous publications( Liu et al, 2020 ; Teng et al, 2020 ), and the acylation reaction site catalyzed by Novozym 435 was specific. The specific reaction equation for the C3(6C)G is shown in Fig.…”
Section: Resultssupporting
confidence: 91%
“…But there were no other ion fragments appeared, which showed that the mother nuclear stability of C3G was strong. Besides, the acylation occurred on glucoside, which was consistent with previous publications( Liu et al, 2020 ; Teng et al, 2020 ), and the acylation reaction site catalyzed by Novozym 435 was specific. The specific reaction equation for the C3(6C)G is shown in Fig.…”
Section: Resultssupporting
confidence: 91%
“…However, the vibrational frequency of biological macromolecules is very complex (Wu et al., 2015), and it is closely related to the geometric arrangement and bond configuration of the fixed molecular groups in the molecule, which also reflects the interaction between molecules (Zaffino et al., 2015). MS is one of the most direct analytical tools to study material structure because it has excellent sensitivity, accuracy, and efficiency (Lang et al., 2021; Teng et al., 2020). X‐ray diffraction technology can provide the most accurate structural information about the complex, but the fact that it can only be used on the crystal of the complex limits its application (Bao et al., 2022).…”
Section: Interaction Between Anthocyanins and Proteinsmentioning
confidence: 99%
“…We need to know the structural categories for subsequent fine confirmation. For the rough judgment of chemical composition, the classical methods include ultraviolet‐visible spectrum (UV‐vis) (Du, Nie, et al, 2022), infrared spectrum (IR) (Du, Zhao, et al, 2022), liquid chromatograph (LC), liquid chromatograph‐mass spectrometer (LC‐MS) (Stavrianidi, 2020; Zhu et al, 2021), gas chromatography (GC), gas chromatography‐mass spectrometer (GC‐MS) (Boateng & Yang, 2021), and thin layer chromatography (TLC) (Teng et al, 2020) (Figure 2). At this level, the combination of new technologies and classical methods for identifying compounds is often in the database.…”
Section: Identification Of Plane Structurementioning
confidence: 99%